How Everyday Products Make People Sick : Toxins at Home and in the Workplace. - Blanc, Paul D., 1951- (University of California Press, 2009)
This book reveals the hidden health dangers in many of the seemingly innocent products we encounter every day--a tube of glue in a kitchen drawer, a bottle of bleach in the laundry room, a rayon scarf on a closet shelf, a brass knob on the front door, a wood plank on an outdoor deck. A compelling exposé, written by a physician with extensive experience in public health and illustrated with disturbing case histories, How Everyday Products Make People Sick is a rich and meticulously documented account of injury and illness across different time periods, places, and technologies.